Cartan-Eilenberg Gorenstein Flat Complexes - Yang, Gang; Liang, Li (Mathematica Scandinavica, 2014)
In this paper, we study Cartan-Eilenberg Gorenstein flat complexes. We show that over coherent rings a Cartan-Eilenberg Gorenstein flat complex can be gotten by a so-called complete Cartan-Eilenberg flat resolution. We argue that over a coherent ring every complex has a Cartan-Eilenberg Gorenstein flat cover.